2021
DOI: 10.1038/s41550-021-01336-w
|View full text |Cite|
|
Sign up to set email alerts
|

Compact pebbles and the evolution of volatiles in the interstellar comet 2I/Borisov

Abstract: The interstellar traveler, 2I/Borisov, is the first clearly active extrasolar comet, ever detected in our Solar system. We obtained high-resolution interferometric observations of 2I/Borisov with the Atacama Large Millimeter/submillimeter Array (ALMA), and multi-color optical observations with the Very Large Telescope (VLT) to gain a comprehensive understanding of the dust properties of this comet. We found that the dust coma of 2I/Borisov consists of compact "pebbles" of radii exceeding ∼ 1 mm, suggesting tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…This confirmed the existence of a galactic population of interstellar objects with spatial number densities of order n o ∼ 1-2 × 10 −1 au −3 (Trilling et al 2017;Laughlin & Batygin 2017;Jewitt et al 2017;Rafikov 2018b;Zwart et al 2018;Do et al 2018;. Object 2I exhibited a dusty coma (Jewitt & Luu 2019;Bolin et al 2020b;Fitzsimmons et al 2019;Ye et al 2020;McKay et al 2020;Guzik et al 2020;Hui et al 2020;Kim et al 2020;Cremonese et al 2020;Yang et al 2021) with typical cometary carbon-and nitrogen-bearing species detected (Opitom et al 2019;Kareta et al 2020;Lin et al 2020;Bannister et al 2020;Xing et al 2020;Aravind et al 2021). It was enriched in CO relative to H 2 O (Bodewits et al 2020;Cordiner et al 2020), indicating formation exterior to the CO snow line in its original protoplanetary disk (Price et al 2021).…”
Section: Introductionsupporting
confidence: 53%
“…This confirmed the existence of a galactic population of interstellar objects with spatial number densities of order n o ∼ 1-2 × 10 −1 au −3 (Trilling et al 2017;Laughlin & Batygin 2017;Jewitt et al 2017;Rafikov 2018b;Zwart et al 2018;Do et al 2018;. Object 2I exhibited a dusty coma (Jewitt & Luu 2019;Bolin et al 2020b;Fitzsimmons et al 2019;Ye et al 2020;McKay et al 2020;Guzik et al 2020;Hui et al 2020;Kim et al 2020;Cremonese et al 2020;Yang et al 2021) with typical cometary carbon-and nitrogen-bearing species detected (Opitom et al 2019;Kareta et al 2020;Lin et al 2020;Bannister et al 2020;Xing et al 2020;Aravind et al 2021). It was enriched in CO relative to H 2 O (Bodewits et al 2020;Cordiner et al 2020), indicating formation exterior to the CO snow line in its original protoplanetary disk (Price et al 2021).…”
Section: Introductionsupporting
confidence: 53%
“…Moreover, Borisov's dust was consistent with grains mostly larger than 100 µm (Kim et al 2020). Yang et al (2021) presented VLT and ALMA observations that showed the presence of 1mm size pebbles in the coma. They measured a CO production rate of Q(CO) = 3.3 ± 0.8 × 10 26 s −1 and found that the CO/H 2 O mixing ratio changed drastically before and after perihelion, implying that the comet's home system experienced efficient radial mixing.…”
Section: Discussionmentioning
confidence: 60%
“…In stark contrast to 'Oumuamua, the interstellar comet Borisov displayed physical characteristics that are broadly consistent with the census of cometary bodies in the solar system. It had dusty cometary activity (Fitzsimmons et al 2019;Jewitt & Luu 2019;Cremonese et al 2020;Guzik et al 2020;Hui et al 2020;Kim et al 2020;McKay et al 2020;Ye et al 2020;Bolin et al 2020b;Yang et al 2021), and early observations confirmed the presence of carbon-and nitrogenbased species in the outflow (Opitom et al 2019;Bannister et al 2020;Kareta et al 2020;Lin et al 2020;Xing et al 2020;Aravind et al 2021). It was particularly enriched in CO (Bodewits et al 2020;Cordiner et al 2020), which could be explained if it formed in the outer regions of a protoplanetary disk (Price et al 2021).…”
Section: Introductionmentioning
confidence: 92%